Diagnosis of Tropheryma whipplei pneumonia using targeted nanopore sequencing: a rare case report and literature review - Yu, Miao; Wang, Wenbin; Chen, Wei; Ye, Kexin; Zhou, Yuqing; Vaishnani, Deep K.; Chen, Chen; Jin, Xuancheng; Zhu, Xiaojun; Ma, Jun; Qian, Fengfei; Zhong, Xiaohua; et al. (Frontiers in Medicine, 2025)
Tropheryma whipplei (TW) pneumonia is a rare disease caused by Tropheryma whipplei infection. Due to the difficulty in obtaining pathogenetic evidence, the misdiagnosis rate is high, posing significant challenges for early diagnosis and treatment. Targeted sequencing technology based on nanopore sequencing technology (tNGS) allows for detecting rare pathogens that are difficult to identify using traditional methods, leading to improved detection rates for TW. This paper reports a case of pneumonia diagnosed as a TW infection through the use of tNGS on bronchoalveolar lavage fluid (BALF), with the patient showing improvement after treatment with sequential administration of meropenem followed by compounded sulfamethoxazole.